The effect of azathioprine (Imuran) on the cell cycle of promonocytes and the production of monocytes in the bone marrow (The Rockefeller University Press, 1975)
The present communication concerns the effect of azathioprine on the mitotic activity of promonocytes and the production of monocytes. In vitro and in vivo labeling with [3H]thymidine showed that during azathioprine treatment the promonocytes synthesize DNA and that, contrary to expectation, the labeling index increases. Cytospectrophotometric determination of the Feulgen-DNA content of the promonocytes during azathioprine treatment showed an increase in the percentage of tetraploid promonocytes, and determination of the various phases of the cell cycle showed significantly increased DNA synthesis and cell cycle times as compared with the normal steady state. On the basis of these results it can be concluded that azathioprine arrests the cell cycle of the promonocytes late in the DNA synthesis phase or in the postsynthesis (G2) phase and mitosis does not occur. This timing of the effect of azathioprine had not been previously observed. The diminished mitotic activity of the promonocytes during azathioprine treatment depressed monocyte production. During treatment with 3 mg/kg azathioprine the cell cycle time of the promonocytes was on the average 5.5 h longer than in the normal steady state and the rate of monocyte production was reduced by 70%. During an acute inflammatory reaction too, monocyte production is affected by azathioprine. In animals not treated with azathioprine but with an acute inflammation the cell cycle time becomes shorter and the monocyte production increases, but animals treated with (3 mg/kg) azathioprine do not show this effect. The kinetics of the monocyte also changes under the low dosage of azathioprine. As consequence of the diminished production of monocytes, far fewer (about 50%) monocytes enter and leave the circulation than during the normal steady state. During an acute inflammatory reaction the numbers in transit through the circulation are slightly augmented but remain considerably lower than in nonazathioprine-trehat of animals not treated with azathioprine.